Directional Spillover of Fossil Fuels Prices on a Hydrothermal Power Generation Market - Oviedo-Gómez, Andrés; Londoño-Hernández , Sandra Milena; Manotas-Duque , Diego Fernando (International Journal of Energy Economics and Policy, 2023)
The Colombian electricity market is based on a hydrothermal power generation market with a strong dependence on exogenous variables such as fossil fuel prices and climatology factors. Besides, the Colombian economy is characterizable by relevant mining-energy activities. Therefore, the main objective of this research was to evaluate the directional spillovers between the electricity spot prices and gas, coal, and crude oil prices and thus provide relevant information for the electricity market agents to identify the risk related to energy commodity price fluctuations. The dataset used in this research consists of monthly logarithmic returns of energy prices between September 2009 and December 2019. The main finding shows that the system's average connectedness is 13,6%. Besides, the electricity spot prices are net shock receivers of volatility, and 20% of their dynamic is related to fossil fuel price fluctuations.